Impacts of acupuncture on postoperative treatment of the anterior cruciate ligament in soccer players (Research, Society and Development, 2021)
Football is a sport where many injuries occur, mainly in the knee, and due to the movement mechanisms of this sport, the ligament most susceptible to these injuries is the anterior cruciate ligament. With the analysis of these data, the present study aims to analyze the importance of acupuncture in the postoperative treatment of anterior cruciate ligament in soccer players, using a literature review using research methods in databases such as PubMed, Scielo, Google Scholar, concluding that acupuncture helps a lot the post-surgical treatment, mainly in pain control and with much better effects when associated with physiotherapy, being able to accelerate the athletes' return to their sports activities. However, it can be emphasized that more studies are needed regarding this theme.